NaCl as a physiological modulator of synthesis of compatible solutes and antioxidant potential in sangam (Clerodendron inerme L.) - S. Natarajan*, N. Silambarasan (Journal of Plant Stress Physiology, 2015)
The present investigation was made to study the effect of different concentrations of sodium chloride on the proline (PRO), glycine betaine (GB), sugar and antioxidant content of the halophytic species, Clerodendron inerme. The plant could survive a wide range of 100-1000 mM of NaCl. The upper limit for the survival of the species was 500 mM. Above 500 mM, the seedlings could not survived. However, favorable growth response by the seedlings was confined to 200 mM NaCl. The accumulation of PRO, GB was more in leaf tissue than the stem and root of NaCl treated plants. PRO, GB content is believed to function as a compatible solute in balancing cytoplasmic and vacuolar water potentials not only due to salinity stress but also under drought, heat and cold stresses. Increasing salinity increased the level of PRO, GB up to the extreme level of 500 mM NaCl. The sugar content decreased in all the three tissues with increasing NaCl up to 200 mM and at higher concentrations, salinity gradually increased the sugar up to 500 mM NaCl. Survival of plants in the saline environment depends on the quantitative ratio between toxic and protective compounds PRO; GB is believed to be one of the protective substances. The non-enzymatic antioxidant contents such as ascorbic acid and Î±-tocopherol were detected under high concentration of 500 mM NaCl. The increase in antioxidant enzyme activity could be the response of cellular damage induced by the NaCl.